2012
DOI: 10.1007/s00404-012-2660-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between periodontal inflammation and fetal growth in pregnant women: a cross-sectional study

Abstract: These results suggest that periodontal inflammation is correlated with fetal femur length, birth weight, and birth length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
1
13
0
2
Order By: Relevance
“…For example, active periodontal inflammation, as determined by bleeding on probing, has been reported to correlate with reductions in fetal femur length, birth weight and birth length (Takeuchi et al. ). Indeed, it has even been suggested that periodontal disease severity may predict adverse pregnancy outcome (Al Habashneh et al.…”
mentioning
confidence: 99%
“…For example, active periodontal inflammation, as determined by bleeding on probing, has been reported to correlate with reductions in fetal femur length, birth weight and birth length (Takeuchi et al. ). Indeed, it has even been suggested that periodontal disease severity may predict adverse pregnancy outcome (Al Habashneh et al.…”
mentioning
confidence: 99%
“…Periodontal disease is a chronic inflammatory disease of the soft and hard tissues that support the teeth, caused by bacterial plaque and influenced by host response factors (Zi et al, 2013;Takeuchi et al, 2013;Muwazi et al, 2013). There are two main types of conditions; gingivitis and periodontitis.…”
Section: Periodontal Disease As a Potential Risk Factor For Adverse Pmentioning
confidence: 99%
“…We chose this marker in part because the “tendency for the gingiva to bleed” was the “decisive criterion” of the Gingival Index (GI) (2). Also, the population of the original GI study was pregnant women (3) and there is a higher prevalence of periodontal inflammation in women during pregnancy compared to non-pregnant women (4, 5). Therefore the aim of this study was to investigate the correlation of a salivary occult blood test (SOBT) with traditional measures from a full mouth periodontal examination (FMPE) in the detection of periodontal inflammation, with the intent to assess the feasibility of the SOBT as a measure of periodontal inflammation in a population of women during pregnancy.…”
Section: Introductionmentioning
confidence: 99%